Pengaruh Kompetensi, Independensi, Profesionalisme dan Etika Terhadap Kualitas Audit (Studi Empiris Pada BPK RI Perwakilan Provinsi Jambi) - Dwi Apriana P; Sri Rahayu; Junaidi Junaidi (Magister Ilmu Akuntansi Universitas Jambi, 2018)
This study aims to examine the influence of competence, independence, professionalism and ethics on audit quality of empirical studies at BPK RI Representative of Jambi Province. The data in this study is the primary data using questionnaires and the strengthening of the discussion is confirmed by the interview. The type of research in this study is quantitative research. The sample in this research is the auditor of BPK RI Representative of Jambi Province as many as 62 people. The analytical method used is descriptive statistical method and hypothesis test by using IBM SPSS. The result of the analysis proves that the competence, independence, professionalism and ethics influence simultaneously to the quality of audit BPK RI Representation of Jambi Province. While partially, competence and independency have no effect on audit quality at BPK RI representatives of jambi province, while professionalism and ethics have an effect on audit quality at BPK RI representatives of jambi province.Keywords: Competence, independence, professionalism, ethics and audit quality